Democratic listening: News podcasts, trust and political participation in Australia. Issue 1 (1st June 2023) - Bird, Dylan
This article illustrates how news podcasts are playing a productive role in animating democracy in Australia. Drawing on findings from an exploratory online survey, it highlights how audiences view news podcasts as an important enabler of their participation in democratic life, and that news podcast listeners are likely to engage in both latent and manifest forms of political action. It also indicates that news podcast listeners are discerning media consumers, and that news podcasts are valued for reasons of both convenience and content. With limited prior research into the relationship between podcast listening and civic engagement, this article provides evidence for how this relatively new podcast genre is prized for its ability to enhance democratic life in Australia. It also problematizes the notion of trust in audio news, signalling a key avenue for further research examining the interplay between traditional markers of journalistic authority and more emotional styles of podcast journalism storytelling.